Hard turning of cold work tool steel using wipper ceramic tool - Mohd. Yusof, Noordin; Mohd. Zainal, Affandi; Hendriko, Hendriko; Kurniawan, Denni (Faculty of Mechanical Engineering, Universiti Teknologi Malaysia, 2008)
While advanced cutting tools used in hard turning applications come with expensive unit price, coated ceramic offers cheaper alternative especially for mid range of hard turning. Wiper geometry featured in coated ceramic tools enabled an increase in productivity or an improved in surface finish despite limited report on this cutting edge modification. In this study, the performance of wiper coated ceramic tool (TiN coating with mixed Al2O3/TiCN substrate) when turning hardened cold work tool steel (54-55 HRC) is evaluated by varying the cutting speed and feed in terms of tool life and surface roughness. The results were compared with those of its conventional geometry counterpart. The wiper tool results in slightly shorter tool life but with much finer surface finish than the conventional one. Design of experiment was used to quantify the effect of cutting parameters on tool life and surface roughness and to determine the optimum cutting parameters that generate the preferred machining results.